2011
DOI: 10.1148/radiol.11101133
|View full text |Cite
|
Sign up to set email alerts
|

Small (≤20 mm) Pancreatic Adenocarcinomas: Analysis of Enhancement Patterns and Secondary Signs with Multiphasic Multidetector CT

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11101133/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
163
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 29 publications
9
163
2
2
Order By: Relevance
“…However, although we did not perform a direct comparison of the imaging features between the two disease entities, the absence of upstream main ductal dilatation, parenchymal atrophy, and perivascular tumor infiltration, which are the typical CT features of primary pancreatic cancer, may be useful differential points between metastatic non-RCC tumors and primary pancreatic tumors [15][16][17][18]. Therefore, if an ill-defined, hypovascular pancreatic tumor is seen without upstream ductal dilatation, parenchymal atrophy, or perivascular tumor infiltration in patients with underlying primary non-RCC tumors, metastatic pancreatic tumor may be another consideration along with a second primary pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, although we did not perform a direct comparison of the imaging features between the two disease entities, the absence of upstream main ductal dilatation, parenchymal atrophy, and perivascular tumor infiltration, which are the typical CT features of primary pancreatic cancer, may be useful differential points between metastatic non-RCC tumors and primary pancreatic tumors [15][16][17][18]. Therefore, if an ill-defined, hypovascular pancreatic tumor is seen without upstream ductal dilatation, parenchymal atrophy, or perivascular tumor infiltration in patients with underlying primary non-RCC tumors, metastatic pancreatic tumor may be another consideration along with a second primary pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al [ 98 ] reported that 27 % of small (≤20 mm) pancreatic adenocarcinomas are isoattenuating at CT, and hence not directly visible without the use of some secondary signs, such as upstream dilation of main pancreatic duct, the double-duct sign, an abrupt cutoff of the main pancreatic duct. Moreover, small well-differentiated pancreatic adenocarcinomas, which are associated with a better survival rate after resection, are isoattenuating in more than 50 % of cases [ 98 -100 ].…”
Section: Isodense Massmentioning
confidence: 99%
“…In this setting, the presence of secondary signs (such as pancreatic duct cut-off, dilatation of the pancreatic duct or common bile duct, upstream atrophy of the parenchyma, and contour abnormalities), could help in diagnosis of pancreatic cancer [ 19 , 25 , 26 ]. A recent study on 163 patients with small pancreatic adenocarcinomas showed that the prevalence of pancreatic cancer accompanied by secondary signs differs signifi cantly according to tumor size: 76 % of tumors smaller than 20 mm and 99 % of tumors between 21 and 30 mm [ 27 ]. The prevalence of isoattenuating pancreatic cancers accompanied by secondary signs was 88 % (14 of [ 27 , 28 ].…”
Section: Computed Tomographymentioning
confidence: 99%